Accelerated hyperfractionation plus temozolomide in glioblastoma. Issue 1 (December 2016) - Kaul, David; Florange, Julian; Badakhshi, Harun; Grün, Arne; Ghadjar, Pirus; Exner, Sebastian; Budach, Volker
Abstract Introduction Hyperfractionated (HFRT) or accelerated hyperfractionated radiotherapy (AHFRT) have been discussed as a potential treatment for glioblastoma based on a hypothesized reduction of late radiation injury and prevention of repopulation. HFRT and AHFRT have been examined extensively in the pre-Temozolomide era with inconclusive results. In this study we examined the role of accelerated hyperfractionation in the Temozolomide era. Materials and methods Sixty-four patients who underwent AHFRT (62 of which received Temozolomide) were compared to 67 patients who underwent normofractionated radiotherapy (NFRT) (64 of which received TMZ) between 02/2009 and 10/2014. Follow-up data were analyzed until 01/2015. Results Median progression-free survival (PFS) was 6 months for the entire cohort. For patients treated with NFRT median PFS was 7 months, for patients treated with AHFRT median PFS was 6 months. Median overall survival (OS) was 13 months for all patients. For patients treated with NFRT median OS was 15 months, for patients treated with AHFRT median OS was 10 months. The fractionation regimen was not a predictor of PFS or OS in univariable- or multivariable analysis. There was no difference in acute toxicity profiles between the two treatment groups. Conclusions Univariable and multivariable analysis did not show significant differences between NFRT and AHFRT fractionation regimens in terms of PFS or OS. The benefits are immanent: the regimen does significantly shorten hospitalization time in a patient collective with highly impaired life expectancy. We propose that the role of AHFRT + TMZ should be further examined in future prospective trials.